Optimizing Mushroom Cultivation Process - Concepts for Control and Monitoring System (Agricultural Engineering, 2020)
The first part of the article contains a basic description of the mushroom production process. The analysis of this process allows to propose algorithms for monitoring the growing conditions and controlling the cultivation process − in the latter case with possible human operator intervention. These algorithms, along with their description, are included in the second part of the article - they can be used in the design and implementation of intelligent mushroom farm management systems.